2002
DOI: 10.1182/blood.v100.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Impact of trisomy 8 (+8) on clinical presentation, treatment response, and survival in acute myeloid leukemia: a Southwest Oncology Group study

Abstract: The prognostic impact of trisomy 8, alone or with other clonal aberrations, was evaluated in 849 patients with previously untreated acute myeloid leukemia (AML) who were registered to 5 Southwest Oncology Group trials. At presentation, 108 (12.7%) patients had ؉8 in their karyotypes, including 43 (5.1%) patients with ؉8 as the sole aberration; 307 (36.2%) were normal, and 434 (51.1%) had other cytogenetic abnormalities. Patients with ؉8 were slightly older (P ‫؍‬ .033), had lower WBC (P ‫؍‬ .011), and had lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
50
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 18 publications
15
50
0
1
Order By: Relevance
“…Also our results, with a median OS of 29 months, compared favorably with those observed with series reporting outcomes of þ 8 AML patients after mixed consolidation regimen (chemotherapy, autologous or allogeneic transplantation) in which median survival did not exceed 16 months. 1 Only four patients had t (15,17) and þ 8 in our series. We kept these four patients for the analyses, as the results did not change (for example, 5-year LFS was 43% excluding those four patients).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Also our results, with a median OS of 29 months, compared favorably with those observed with series reporting outcomes of þ 8 AML patients after mixed consolidation regimen (chemotherapy, autologous or allogeneic transplantation) in which median survival did not exceed 16 months. 1 Only four patients had t (15,17) and þ 8 in our series. We kept these four patients for the analyses, as the results did not change (for example, 5-year LFS was 43% excluding those four patients).…”
Section: Discussionmentioning
confidence: 64%
“…1 The prognostic effect of þ 8 as a sole chromosomal abnormality in AML remains debated and was found in the literature to be associated either with an intermediate or a poor prognosis. [1][2][3] The results of the Medical Research Council-AML10 trial has assigned AML patients with isolated þ 8 in the 'intermediate' cytogenetic abnormality risk group, showing a 3-year OS and relapse risk of 42 and 42%, respectively. This study suggested also a worsened outcome for these patients in comparison with other cytogenetic abnormality risk group categories within this heterogeneous 'intermediate' prognosis group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological and clinical significance of trisomy 8 in AML remains unclear. 5,[25][26][27] In MDS, trisomy 8 is present only in progenitors and is lacking in long-term repopulating cells capable of engraftment in NOD-SCID mouse systems. In contrast del (5q) is present in the most primitive stem/progenitor cell population.…”
Section: Cytogenetic Subgroupmentioning
confidence: 99%
“…5 The intermediate prognosis group is heterogeneous and includes cases with normal karyotype (NK) (40-50% of AML) 6 and trisomy 8, among others. 7 Lately, several studies have focused on the importance of searching for specific receptor tyrosine kinase mutations, such as tandem duplications in FLT3 or mutations in NPM1, [8][9][10][11][12] as markers of prognosis in AML.…”
Section: Introductionmentioning
confidence: 99%